Design, analysis, and experiment of a new modularized multi-stage rice straw crusher - Jie Wang; Longlong Tu; Pengfei Su; Zhifang Zhu; Pengcheng Liu; Yizheng Dai; Lu Wang (Advances in Mechanical Engineering)
Existing agricultural practices generate a lot of straw, and the common and effective solution of crushing the straw and returning it to the field has problems with the crushing equipment, such as its large size, low power output ratio, and blades jamming. A new modularized multi-stage rice straw crusher was developed featuring material conveying, synchronous feeding chopping, and secondary crushing modules. Using Box-Behnken design with Design-Expert V10.0.7, crushing efficiency (targeting 30 mm particle size, 82.31%) and power consumption (2103.7 W) were optimized via response surface methodology. Optimal parameters included primary chopping at 0.274 m/s, secondary crushing at 26.72 rad/s, and chain drive at 0.083 m/s. Experimental validation showed 84.19% crushing efficiency and 2076.24 W power consumption, with relative errors of 1.88% and 27.5 W respectively, demonstrating synergistic improvement in anti-jamming capability and energy-efficient crushing. This study provides theoretical guidance for enhancing straw processing equipment performance.